Pengaruh Pelatihan Kerja Dan Pembelajaran Online Terhadap Kinerja Dimediasi Oleh Motivasi Kerja Guru Di Sekolah Gamaliel Makassar - Suppu, Yohanis; Muhammadin, Akhmad; Kanto, Muklis (Jurnal Riset Akuntansi dan Manajemen Malahayati (JRAMM), 2023)
This study aims to determine the effect of job training online learning on performance mediated by the work motivation of teachers at the Gamaliel School Makassar.The sample in this study using a saturated sample was 52 teachers. The research results show that: (1) Job training has a positive and significant effect on teacher work motivation. (2) Online learning has a negative and insignificant effect on teacher work motivation. (3) Job training has a positive and significant effect on teacher performance (4). Online learning has a positive and insignificant effect on teacher performance. (5) Work motivation has a positive and significant effect on teacher performance. (6) Job training has a positive and significant effect on teacher performance mediated by teacher work motivation. (7) Online learning has no effect on teacher performance mediated by work motivation. with job training, online learning systems and work motivation, it must be consistently carried out as part of increasing the ability of teachers which will improve the quality of performance and the quality of service in schools.